Prospective evaluation of two iStent® trabecular stents, one iStent Supra® suprachoroidal stent, and postoperative prostaglandin in refractory glaucoma: 4-year outcomes - Myers, Jonathan S.; Auffarth, Gerd U. (Advances in therapy, 2018)
Introduction: This study evaluates long-term outcomes of two trabecular micro-bypass stents, one suprachoroidal stent, and postoperative prostaglandin in eyes with refractory open angle glaucoma (OAG). Methods: Prospective ongoing 5-year study of 80 eligible subjects (70 with 4-year follow-up) with OAG and IOP ≥ 18 mmHg after prior trabeculectomy and while taking 1-3 glaucoma medications. Subjects received two iStent® trabecular micro-bypass stents, one iStent Supra® suprachoroidal stent, and postoperative travoprost. Postoperative IOP was measured with medication and annually following medication washouts. Performance was measured by the proportion of eyes with ≥ 20% IOP reduction on one medication (the protocol-specified prostaglandin) versus preoperative medicated IOP (primary outcome); and the proportion of eyes with postoperative IOP ≤ 15 and ≤ 18 mmHg on one medication (secondary outcome). Additional clinical and safety data included medications, visual field, pachymetry, gonioscopy, adverse events, visual acuity, and slit-lamp and fundus examinations. Results: Preoperatively, mean medicated IOP was 22.0 ± 3.1 mmHg on 1.2 ± 0.4 medications, and mean unmedicated IOP was 26.4 ± 2.4 mmHg. Postoperatively, among eyes without later cataract surgery, mean medicated IOP at all visits through 48 months was ≤ 13.7 mmHg (≥ 37% reduction), and annual unmedicated IOP was ≤ 18.4 mmHg (reductions of ≥ 30% vs. preoperative unmedicated IOP and ≥ 16% vs. preoperative medicated IOP). At all postoperative visits among eyes without additional surgery or medication, ≥ 91% of eyes had ≥ 20% IOP reduction on one medication versus preoperative medicated IOP. At month 48, 97 and 98% of eyes achieved IOP ≤ 15 and ≤ 18 mmHg, respectively, on one medication. Six eyes required additional medication, no eyes required additional glaucoma surgery, and safety measurements were favorable throughout follow-up. Conclusion: IOP control was achieved safely with two trabecular micro-bypass stents, one suprachoroidal stent, and postoperative prostaglandin. This microinvasive, ab interno approach introduces a possible new treatment option for refractory disease.